Diffraction properties of transmission binary blazed grating - Zhou, Hui-Jun; Wang, Qu-Quan (Oficyna Wydawnicza Politechniki Wrocławskiej, 2006)
The properties of binary blazed grating were theoretically analyzed with finite-difference time-domain (FDTD) method. The diffraction efficiencies and diffraction angles of –1, 0, and +1 order for the grating varying with wavelength, grating structure, and the etch depth were studied when the incident angle was 30°. The numerical simulations revealed that the binary blazed grating presented high stability of diffraction efficiencies with wavelength shift.
Optica Applicata, Vol. 36, 2006, nr 1, s. 105-109
Keywords: optyka; binary blazed grating; diffraction efficiency